Safe hierarchical virtual network mapping method based on clustering - Xie LU; Lei XU; Manjun ZHANG (Dianxin kexue)
Based on the 5G network environment, a security hierarchical virtual network mapping method based on K-means clustering was proposed.In particular, the idea of node security classification and the combination of K-menas clustering algorithm was involved to solve the key problems of low security and low mapping efficiency existing in current virtual network mapping.Compared with traditional methods, this research method improves the efficiency of virtual node mapping and enhances the network resilience.